2013
DOI: 10.5851/kosfa.2013.33.5.572
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Sensory Properties of Restructured Jerky with Four Additives

Abstract: This study was carried out to evaluate the effect on properties of restructured jerky by the addition volume of additives. The treatments were divided into glutinous rice flour, potato starch, soybean and acorn powder. Moisture content, water activity (a w ), thiobarbituric acid reactive substances (TBARS), color, yield and sensory evaluation were performed. The moisture contents of four types of restructured jerkies were in the range of 8.92-12.47%, and were lower than that of the control (17.92%). Water acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Jerky also has several benefits such as; being light, portable, and rich in nutrients, which has led to a recent increase in consumption due to the expansion of its purpose of use into sports and outdoor products ( Choi et al , 2008 ). Contrary to the traditional manufacturing method which used the whole muscle, recently, restructuring method has been widely used to utilize various raw materials, low price parts, ( Choi et al ., 2008 ) and to readily add functional materials and non-meat sources ( Han, 2011 ; Ku et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jerky also has several benefits such as; being light, portable, and rich in nutrients, which has led to a recent increase in consumption due to the expansion of its purpose of use into sports and outdoor products ( Choi et al , 2008 ). Contrary to the traditional manufacturing method which used the whole muscle, recently, restructuring method has been widely used to utilize various raw materials, low price parts, ( Choi et al ., 2008 ) and to readily add functional materials and non-meat sources ( Han, 2011 ; Ku et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water activity is one of the important factors related to the classification standard for dehydrated food. In general, the water activity of semi-dried food usually ranges from 0.60-0.90, which is considered to be relatively safe against microorganisms ( Ku et al ., 2013 ). The effects of replacing sucrose with sugar alcohols on the water activity and moisture content of the semi-dried jerkies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…25 [3,4]; [2,16]; [5,7,[17][18][19]; [20,21]; [8,22]; [23,24]; , [25]; [26,27]; [6]; [28]; [29]; [30]; [31]; [25]; [32] Additive substances and their effect 2007-2022 8 [33]; [34]; [35]; [36]; [37]; [38]; [39]; [40] Beef Jerky Processing and Storage 2020-2021 2 [41];; [42];…”
Section: -2023mentioning
confidence: 99%
“…The additional components not only contribute to the enhanced flavour and safety of the finished meat products, but they also have the potential to contribute to the health benefits of the meat products. Ku, et al [35] demonstrated that the restructured jerky that contained glutinous rice flour, potato starch, soybean, and acorn powder was able to effectively reduce the amount of moisture content, water activity, thiobarbituric acid reactive substances (TBARS), and damp yield. According to the results of the sensory evaluations, the product samples that contained 9% glutinous rice flour, potato starch, and chestnut powder had the highest overall approval.…”
Section: Additive Substances and Their Effectmentioning
confidence: 99%